Displacing blackness : power, planning, and race in twentieth-century Halifax - Rutland, Ted (University of Toronto Press, 2018)
While focused on twentieth-century Halifax, Displacing Blackness develops broad insights about the possibilities and limitations of modern planning. Drawing connections between the history of planning and emerging scholarship in Black Studies, Ted Rutland positions anti-blackness at the heart of contemporary city-making.